2017
DOI: 10.1111/jam.13518
|View full text |Cite
|
Sign up to set email alerts
|

Deletingpckimproves growth and suppresses by-product formation during 1,3-propanediol fermentation byKlebsiella pneumoniae

Abstract: This study is the first to identify the critical role of PEP carboxylation, as well as those of PPC and PCK, which are responsible for this reaction, in Kl. pneumoniae. In addition, the pck-deficient mutant was proven to be a valuable 1,3-propanediol producer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The byproducts are difficult to eliminate completely no matter through genetic modification or process optimization, because they are terminal products in the pathways of NADH and ATP synthesis. 16,17 However, the fermentation process could be regulated and optimized to improve the 1,3-PDO production. pH fluctuation strategy was applied to reduce byproducts and enhance 1,3-PDO production by Ji et al 18 Electric method was also used by Xafenias et al to increase 1,3-PDO production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The byproducts are difficult to eliminate completely no matter through genetic modification or process optimization, because they are terminal products in the pathways of NADH and ATP synthesis. 16,17 However, the fermentation process could be regulated and optimized to improve the 1,3-PDO production. pH fluctuation strategy was applied to reduce byproducts and enhance 1,3-PDO production by Ji et al 18 Electric method was also used by Xafenias et al to increase 1,3-PDO production.…”
Section: Introductionmentioning
confidence: 99%
“…The byproducts are difficult to eliminate completely no matter through genetic modification or process optimization, because they are terminal products in the pathways of NADH and ATP synthesis . However, the fermentation process could be regulated and optimized to improve the 1,3‐PDO production.…”
Section: Introductionmentioning
confidence: 99%
“…Thapa et al attempted to knock out the mdh gene encoding malate dehydrogenase to inhibit succinate production and further enhance 2,3-BDO production and then showed that 2,3-BDO was not significantly enhanced (Thapa et al 2019 ). Among the metabolic pathways of succinate synthesis in microorganisms, the main pathway is the carboxylation of phosphoenolpyruvate to oxaloacetate, followed by the generation of succinate from oxaloacetate via the reduction branch of the tricarboxylic acid cycle (Zhang et al 2017 ). The ppc -encoded phosphoenolpyruvate carboxylase is an important enzyme responsible for the carboxylation reaction of phosphoenolpyruvate, a compound reaction that converts phosphoenolpyruvate (C3 metabolite) into a centrally metabolized C4 metabolite (Zhang et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 Deletion of the pck gene encoding phosphoenolpyruvate carboxykinase to reduce the formation of phosphoenolpyruvate can also be helpful in reducing pyruvate and acetate accumulation. 32 Alternatively, Wang et al tried to introduce a polyhydroxybutyrate (PHB) synthesis pathway in K. pneumoniae which provided another route to consume acetyl-CoA and was shown to be useful for reducing acetate accumulation. 33 Although K. pneumoniae is an efficient chassis for 1,3-PDO production, it is a conditionally pathogenic microorganism and its industrial application is limited in some countries.…”
Section: Engineering Of Natural Producersmentioning
confidence: 99%
“…The glycerol-based production systems using natural or engineered 1,3-PDO producers (K. pneumoniae or C. butyricum) still accumulate different kinds of byproducts. 32,53 Although it is principally possible to develop a homo-1,3-PDO production system by eliminating all byproduct formation pathways and activating the TCA cycle, it is very challenging to completely eliminate the complex native metabolic regulation. Blocking all pathways leading to byproduct formation often significantly disturbs cellular metabolism, resulting in retarded cell growth and reduced productivity.…”
Section: Summary and Prospectsmentioning
confidence: 99%